Farid Esack's Hermeneutics and the Contextualization of Religious Texts: A Response to Social Inequality - Fathin Fauhatun (Islamic Thought Review, 2025)
This study explores Farid Esack’s hermeneutical approach to the contextualization of religious texts and its relevance in addressing social inequality. The research aims to analyze how Esack’s interpretive framework integrates liberation theology with Qur’anic exegesis to construct a socially engaged understanding of Islam. By adopting a qualitative library research design combined with conceptual analysis, this study examines Esack’s core principles, including his emphasis on historical consciousness, ethical responsibility, and the progressive nature of revelation. The analysis identifies three main components of Esack’s hermeneutics: the prioritization of marginalized voices in interpretation, the call for theological discourse to transcend metaphysical speculation and engage with concrete socio-political realities, and the insistence on praxis as an inseparable dimension of faith. The findings indicate that Esack advocates a liberationist reading of scripture, positioning theology as a normative framework for ethical action and structural transformation within pluralistic societies. These insights underscore the potential of Esack’s hermeneutics as a critical response to contemporary issues of justice and inequality. This study contributes to the broader discourse on Islamic hermeneutics, social ethics, and liberation theology by offering a conceptual model that bridges scriptural interpretation with commitments to social justice and human dignity.